(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Developing an “engineering way of thinking” is a major goal in engineering education. One promising pedagogical approach is having students create technical models (physical, schematic, or simulation-based) as part of their learning. This research investigates how engaging students in technical model creation influences their engineering thinking skills. To examine the whether and how modeling tasks enhance aspects of engineering thinking (e.g. systems thinking, structural/functional reasoning, iterative design) in undergraduate engineering students. Engaging students in creating technical models supports growth in engineering-thinking capacities. Recommendations for curriculum design and further research are discussed.